2021
DOI: 10.1021/acs.jcim.1c00766
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Control of Structural Mimicry and Mutational Escape in the SARS-CoV-2 Spike Protein Complexes with the ACE2 Decoys and Miniprotein Inhibitors: A Network-Based Approach for Mutational Profiling of Binding and Signaling

Abstract: We developed a computational framework for comprehensive and rapid mutational scanning of binding energetics and residue interaction networks in the SARS-CoV-2 spike protein complexes. Using this approach, we integrated atomistic simulations and conformational landscaping of the SARS-CoV-2 spike protein complexes with ensemble-based mutational screening and network modeling to characterize mechanisms of structure−functional mimicry and resilience toward mutational escape by the ACE2 protein decoy and de novo d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 111 publications
0
48
0
Order By: Relevance
“…Computational and biophysical kinetics studies of the SARS-CoV-2 S trimer interactions with ACE2 using the recent crystal structures also provided important insights into the key determinants of the binding affinity and selectivity [92][93][94][95]. Our recent studies combined simplified and atomistic MD simulations with coevolutionary analysis and network modeling to present evidence that the SARS-CoV-2 spike protein function as an allosterically regulated machine that exploits the plasticity of allosteric hotspots to finetune response to antibody binding [96][97][98][99][100][101][102][103][104][105]. These studies showed that examining the allosteric behavior of the SARS-CoV-2 spike proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data.…”
Section: Introductionmentioning
confidence: 96%
“…Computational and biophysical kinetics studies of the SARS-CoV-2 S trimer interactions with ACE2 using the recent crystal structures also provided important insights into the key determinants of the binding affinity and selectivity [92][93][94][95]. Our recent studies combined simplified and atomistic MD simulations with coevolutionary analysis and network modeling to present evidence that the SARS-CoV-2 spike protein function as an allosterically regulated machine that exploits the plasticity of allosteric hotspots to finetune response to antibody binding [96][97][98][99][100][101][102][103][104][105]. These studies showed that examining the allosteric behavior of the SARS-CoV-2 spike proteins may be useful to uncover functional mechanisms and rationalize the growing body of diverse experimental data.…”
Section: Introductionmentioning
confidence: 96%
“…This study suggested that SARS-CoV-2 S protein may exploit plasticity of specific allosteric hotspots to generate escape mutants that alter response to antibody binding without compromising activity of the spike protein [ 139 ]. A computational approach for rapid mutational scanning of binding energetics and residue interaction networks in the SARS-CoV-2 spike protein complexes was recently proposed [ 140 ]. Using this approach, we integrated atomistic simulations and conformational landscaping of the SARS-CoV-2 spike protein complexes with the ensemble-based mutational screening and network modeling to characterize mechanisms of structure-functional mimicry and resilience to mutational escape by the ACE2 protein decoy and de novo designed miniprotein inhibitors [ 140 ].…”
Section: Computational Studies Of Sars-cov-2 S Protein Binding Mechan...mentioning
confidence: 99%
“…A computational approach for rapid mutational scanning of binding energetics and residue interaction networks in the SARS-CoV-2 spike protein complexes was recently proposed [ 140 ]. Using this approach, we integrated atomistic simulations and conformational landscaping of the SARS-CoV-2 spike protein complexes with the ensemble-based mutational screening and network modeling to characterize mechanisms of structure-functional mimicry and resilience to mutational escape by the ACE2 protein decoy and de novo designed miniprotein inhibitors [ 140 ]. Collectively, our computational studies offered evidence that the SARS-CoV-2 spike protein can function as an allosterically regulated machine that exploits plasticity of allosteric hotspots to fine-tune response to antibody binding [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ].…”
Section: Computational Studies Of Sars-cov-2 S Protein Binding Mechan...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we further expand on our previous studies showing that the SARS-CoV-2 S protein can function as a robust and efficient allosteric regulatory engine that can exploit the intrinsic plasticity of functional regions and versatility of allosteric hotspots to modulate specific regulatory and binding functions. 8994 We propose that Omicron mutational sites can act in a cooperative manner and through allosteric-based mechanism control balance and trade-offs between conformational plasticity, protein stability, and functional adaptability. To overcome limitations associated with the cost of atomistic simulations for the multiple full-length SARS-CoV-2 S Omicron structures, we employed a range of methods based on efficient coarse-grained (CG) simulations and high resolution atomistic graph models combined with dynamic network analysis.…”
Section: Introductionmentioning
confidence: 99%